Forms of conceiving the city of the XX century: space, substance or environment? - Kapustin, Petr (project baikal, 2021)
In the XX century, the city became a problem and challenge to a new, developing urban design consciousness. At first, rational approaches to the city promised bright prospects, which can still be felt today in the graphics of Le Corbusier or L. Hilberseimer. However, only the Renaissance could afford conceiving the city in only one perspective. The XX century needs comprehensive technologies, but the most advanced system of calculation, regulation and control should be based on something that generates the very idea of the city. Fruitless technologies taken as tools need to be boosted by creative, inspiring, although nonstrict, ideas. The nature and metamorphoses of such ideas are discussed in the article.